Palestinian Berlin. Perceptions and Use of Public Space. - Wari, Shahd (LIT, 2017)
How do Palestinian immigrants perceive and use the public space in the city of Berlin? Is their perception and use of space homogenous as a group? What are the main patterns of their socio-spatial practices in public spaces? How do they influence the urban landscape of the neighborhoods in which they live? Which factors play a role in their perception and use of public space and how do the hybrid identities of the second and third generations affect their socio-spatial behavior in comparison to the first generation? This book aims to present a study about Palestinian immigrants in Berlin and answer these questions and more about Palestinian identity, socio-spatial practices and use of public space.
Keywords: Stadtforschung; Öffentlicher Raum; Nutzung; Bevölkerungsgruppe; Migration; Integration; Einwanderung; Wahrnehmung; Befragung; Zweite Einwanderergeneration; Palästinenser; Kulturelle Identität